Protective effect of irisin against Alzheimer’s disease - Chen, Kang; Wang, Kun; Wang, Tianhui (Frontiers in Psychiatry, 2022)
Despite being one of the greatest global challenges for health and social care in the 21st century, Alzheimer’s disease (AD) lacks specific medicine. Irisin, an exercise-generated muscle factor, emerges as a potential hormone for AD prevention and treatment because of its role in promoting the browning of white adipose tissue, accelerating energy expenditure, regulating energy metabolism, and improving insulin resistance. The paper reviews classic hallmarks of AD and irisin’s physiology before the possible mechanism by which irisin protects against AD is discussed in terms of its effects related to molecular biology and cellular biology. Results reveal that irisin sharpens learning memory by inducing the production of brain derived neurotrophic factor (BDNF), lowers the production of inflammatory factors, protects neurology through astrocytes, and ameliorates AD symptoms by improving insulin resistance. The review aims to facilitate future experimental studies and clinical applications of irisin in preventing and treating AD.